Issues occult hepatitis B virus infection - I. A. Morozov; L. Yu. Ilchenko; N. I. Gromova; I. G. Fyedorov; I. V. Gordeychuk; A. K. Knyazhentseva; E. V. Zverkova; M. I. Mikhaylov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2012)
Aim of investigation. With the help of up-to-date molecular-biological and morphological methods to determine frequency of the occult form of chronic hepatitis B (CHB) among HBsAg-negative patients with chronic liver diseases (CLD) of various etiology and to present clinical and morphological characteristic.Material and methods. Overall 168 patients were investigated. Of 60 patients with anti-HBcAg antibodies 35 patients without HBsAg and DNA HBV in blood serum have been selected, who underwent fine-needle transcutaneous liver biopsy. Molecular biologic enzymelinked immunoassay (ELISA), polymerase chain reaction (PCR) and morphological (immunohistochemistry, electron microscopy) methods were utilized for diagnostics.Results. Novel two-stage algorithm of diagnostics of CHB occult form was developed. Morphological criteria, typical for obscure HBV-monoinfections and HCV coinfection are described. With the help of immunohistochemistry and electron microscopy in all patients with anti-HBcAg antibodies in serum and absence of HBsAg and DNA HBV, presence of HBV virions in liver tissue was revealed. HBV and HCV coinfection was accompanied by more severe (in comparison to monoinfection) immune inflammatory response. In 80% of cases presence of TT-like mini virus (TTMV) in blood lymphoid elements was revealed, in two patients this virus was detected in hepatocyte nucleus that proves its hepatotropic properties.Conclusions. Frequency of the occult form of hepatitis B among CLD patients is no less than 20%. It was found, that anti-НВсAg antibodies can be effective, though «surrogate» marker of HBV-infection.